Inovasi Pendidikan Sebagai Solusi dalam Mengatasi Permasalahan Pendidikan di Indonesia (International Forum of Researchers and Lecturers, 2024)
Educational innovation is the application of new ideas, methods or technology in the field of education which aims to improve the learning process, expand access to education and improve learning outcomes. This innovation involves changes to teaching approaches, curriculum, evaluation, and school management to create a more effective learning environment. This research aims to analyze and examine various theories and research results on educational innovation in Indonesia. This research uses qualitative research methods with literature studies. The results of this research include (1) Educational Innovation, (2) Innovation to overcome Educational problems, (3) Quality of Educational Innovation, (4) Development of Educational Innovation, (5) Position of Educational Innovation, (6) Role of Educational Innovation, (7) Discussion of Innovation in Technology, (8) The Role of Innovation Management, (9) Learning Innovation, (10) Implementation of Innovation Power-based Education.